Content Analysis of Elderly Education Policies in China: From the Perspective of Policy Instruments (1982–2021) - Mochang Qiu; Weidong Wang (Complexity)
Population aging has emerged as a social issue in most countries worldwide. Developing education for the elderly is one of the key strategies to combat the challenges of an aging population. Based on the two-dimensional analysis framework of the policy instruments and the type of elderly education, the content analysis method was used to analyze 49 elderly education policy documents developed and issued in China over the last four decades in this study. This study aims to provide a reference for the formulation of education policies for the elderly in China and other countries. The results indicated that the allocation of policy instruments was inconsistent between and within types. It is imperative to issue new programmatic documents, optimize the allocation of policy instruments, and enhance their adaptability, thereby boosting the development of elderly education.